A low symptomatic form of neurodegeneration in younger carriers of the FMR1 premutation, manifesting typical radiological changes. Issue 3 (5th December 2007) - Loesch, D Z; Cook, M; Litewka, L; Gould, E; Churchyard, A; Tassone, F; Slater, H R; Storey, E
Abstract : Fragile X-associated tremor/ataxia (FXTAS) is a late onset disorder caused by a premutation in the FMR1 gene, in which neurological symptoms are associated with white matter ( wm ) changes, especially within the middle cerebellar peduncles (MCP sign), seen on magnetic resonance images (MRIs). We report a discrepancy between obvious radiological presentations and minimal clinical involvement in two younger male premutation carriers. These carriers, aged 52 and 39 years, showed distinct MCP sign, but reported no neurological symptoms. If this discrepancy represents the initial stage of FXTAS, our findings suggest the possibility of early diagnosis from MRI scans.